2011
DOI: 10.1002/ijc.26141
|View full text |Cite
|
Sign up to set email alerts
|

Methylseleninic acid downregulates hypoxia‐inducible factor‐1α in invasive prostate cancer

Abstract: Alternative strategies are needed to control growth of advanced and hormone refractory prostate cancer. In this regard, we investigated the efficacy of methylseleninic acid (MSeA), a penultimate precursor to the highly reactive selenium metabolite, methylselenol, to inhibit growth of invasive and hormone refractory rat (PAIII) and human (PC-3 and PC-3M) prostate cancer cells. Our results demonstrate that MSeA inhibits PAIII cell growth in vitro as well as reduces weights of tumors generated by PAIII cells trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
(47 reference statements)
2
27
0
Order By: Relevance
“…Consistent with our data, published results show the degradation of constitutively expressed HIF-1α in prostate cancer [38] and hypoxia induced HIF-1α in B-cell lymphoma [39] by selenium. These findings show that both hypoxia induced and constitutively expressed HIF-α are inhibited by selenium suggesting that selenium could inhibit growth of tumors expressing HIF-1α, HIF-2α or both.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our data, published results show the degradation of constitutively expressed HIF-1α in prostate cancer [38] and hypoxia induced HIF-1α in B-cell lymphoma [39] by selenium. These findings show that both hypoxia induced and constitutively expressed HIF-α are inhibited by selenium suggesting that selenium could inhibit growth of tumors expressing HIF-1α, HIF-2α or both.…”
Section: Discussionsupporting
confidence: 93%
“…Our recent report [22] and study by Sinha et al, [38] demonstrated stabilization of PHDs by MSA leads to the degradation of HIF-1α. HIF-1α degradation through VHL dependent and independent pathways is known.…”
Section: Discussionmentioning
confidence: 96%
“…Overexpression of HIF-1α has been detected in >70% of solid tumors. While upregulation or activation of HIF-1α promotes tumor growth, downregulation or loss of HIF-1α activity has been demonstrated to markedly decrease tumor growth, vascularization and energy metabolism (8)(9)(10)(11). The suppression of HIF-1α expression by RNA interference (RNAi) has been shown to be an effective method of cancer therapy (12).…”
Section: Introductionsupporting
confidence: 46%
“…Two weeks after PAIII cells were injected through the tail vein, rats received daily MSA supplementation for two weeks. This treatment significantly reduced the metastatic lung foci found in the MSA-fed rats [68]. This particular experiment did not address the effect of MSA on primary tumors or the events that happen before cancer cells arrive in the secondary organs.…”
Section: Prostate Cancermentioning
confidence: 99%